A Mixed-Methods Approach to Investigating Social and Emotional Learning at Schools: Teachers’ Familiarity, Beliefs, Training, and Perceived School Culture - Schiepe-Tiska, Anja; Dzhaparkulova, Aiymbubu; Ziernwald, Lisa (Frontiers in Psychology, 2021)
Education advocates argue that effective schools should foster multidimensional educational goals that not only include cognitive but also non-cognitive outcomes. One important non-cognitive outcome are social and emotional skills. Previous research showed that for enhancing students’ social and emotional learning one of the most important factor is the teacher. Hence, the present study investigated teachers’ familiarity, beliefs, training, and perceived school culture with regard to social and emotional learning and its facets self-awareness, self-management, and social-awareness by applying a parallel convergent mixed-method design. We conducted in-depth interviews and an online survey with mainly secondary teachers from different countries. The reason for collecting both qualitative and quantitative data was to obtain different but complementary data on the same topic in order to bring greater insight into this research question than would be obtained by either type of data separately. Teachers reported an uncertainty and a lack of professional skills and knowledge in delivering SEL instructions that was particularly low for self-awareness and self-management. Therefore, in both study parts, teachers expressed strong interest in receiving professional SEL training. However, schools rarely provide resources (instruction materials, specific courses or activities) or create conditions (training teachers, devoting teaching hours, increasing number of councilors at schools, receiving school administration support), that would promote teachers’ instruction of SEL. The results do not only add to researchers’ knowledge about teachers’ SEL familiarity, beliefs, training, and school culture, but are also relevant for policymakers, administrators, and school staff by identifying critical aspects that prevent successful social and emotional learning in schools.